Reproductive health of Roma women in Slovakia - Šupínová, Mária; Sonkolyová, Gabriela; Klement, Cyril (Central European journal of public health, 2020)
OBJECTIVE: In most indicators of the way of life, the Roma community is generally different from the majority population and dominant culture. The objective of the study was to describe factors affecting the health of the Roma living in Slovakia, with an emphasis on the sexual and reproductive health of Roma women, and report on the results of analysis of high-risk pregnancies of Roma women in the district of Rimavská Sobota, Slovakia. METHODS: A retrospective study of medical documentation was used. The results were analyzed using the absolute and relative frequencies. Statistical methods were used. RESULTS: A total of 1,256 high-risk pregnancies were analyzed, of which 622 (49.52%) were in Roma women. The average age of Roma respondents was lower by 5 years compared to non-Roma. The age of Roma women at the first pregnancy was statistically significantly lower compared to non-Roma (p < 0.001). The Roma respondents achieved statistically significantly lower levels of education than non-Roma. There was a demonstrably higher number of pregnancies as well as a higher number of artificial and spontaneous abortions per Roma woman. These results were statistically significant. For Roma women, pregnancy began to be risky demonstrably earlier than for non-Roma (p < 0.001). There was a statistically significant difference in attending prenatal counselling. Roma women attended prenatal counselling statistically significantly less frequently than non-Roma (p < 0.001). A significant statistical dependence was found between attending prenatal counselling and the onset of pregnancy problems in Roma women. There was no significant difference in the incidence of other diseases associated with high-risk pregnancy among Roma and non-Roma respondents. CONCLUSION: The findings indicate that Roma women are exposed to health problems in the area of sexual and reproductive health in Slovakia. In the approach to the Roma, it is essential to focus on improving accessibility to health care, prevention, knowledgeableness and effectively preventing, eradicating and strongly penalizing all forms of discrimination in access to health care, especially for Roma women, who are more likely to receive health care.
Keywords: parita; Adolescent; risk factors; rizikové těhotenství; Adult; Pregnancy; Prenatal Care; Parity; reproductive health; Retrospective Studies; lidé; Slovenská republika; sociální determinanty zdraví; Humans; Romové; retrospektivní studie; Roma; reprodukční zdraví; Abortion, Induced; Young Adult; socioekonomické faktory; prenatální péče; high-risk pregnancy; Pregnancy, High-Risk; rizikové faktory; Reproductive Health Services; Pregnancy Complications; dospělí; Reproductive Health; Socioeconomic Factors; mladý dospělý; komplikace těhotenství; služby v oblasti reprodukčního zdraví; samovolný potrat; ženské pohlaví; mladiství; Social Determinants of Health; těhotenství; Female; Abortion, Spontaneous; Risk Factors; indukovaný potrat; Slovakia